Highway Franchising and Real Estate Values - Eduardo Engel; Ronald Fischer; Alexander Galetovic (Yale University, Economic Growth Center, 2002)
It has become increasingly common to allocate highway franchises to the bidder that offers to charge the lowest toll. Often, building a highway increases the value of land held by a small group of developers, an effect that is more pronounced with lower tolls. We study the welfare implications of highway franchises that benefit large developers, focusing on the incentives developers have to internalize the effect of the toll they bid on the value of their land. We study how participation by developers in the auction affects equilibrium tolls and welfare. We find that large developers bid more aggressively than construction companies that own no land. As long as land ownership is sufficiently concentrated, allowing developers in the auction leads to lower tolls and higher welfare. Moreover, collusion among developers is socially desirable. We also analyze the case when the franchise holder can charge lower tolls to those buying her land ('toll discrimination'). Relative to uniform tolls, discrimination decreases welfare when land is highly concentrated, but increases welfare otherwise. Finally, we consider the welfare implications of subsidies and bonuses for proposing new highway projects.
Keywords: D44; H40; H54; R42; R48; 330; Demsetz auctions; highway concessions; private participation in infrastructure; Öffentlich-private Partnerschaft; Autobahn; Bodenpreis; Theorie; Chile